Cache and Carry: lithic technology and Mesolithic mobility - Paul R. Preston (Internet Archaeology, 2009)
Using chipped stone data derived from the analyses of trans-Pennine Mesolithic assemblages and Clark's (1954) Star Carr assemblage, this article will examine the influence of lithic technology within the mobility strategies of the Mesolithic hunter-gatherers in Northern England. In particular it will explore the possible association between persistent places (Barton et al. 1995) as resource locales in the landscape and their influence on raw material consumption and tool manufacture. Key to this study is the introduction (into the Chaîne Opératoire model of lithics analyses) of the notion of 'Equipotentiality' (Preston 1999), which is derived from the biological term Exaption (Gould and Vrba 1982). This new term will be defined and explored in relation to hunter-gatherer mobility strategies, along with other processes such as retooling (e.g. Hoffman 1992) or resharpening. A model for equipotential tool use at both site and landscape levels, together with its influence on hunter-gatherer mobility strategies, is proposed.